Towards Just Geographies of Academic Mobilities - Hopkins, Debbie (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
Just geographies of academic mobilities recognize the complicity of some forms of academic work with fossil fuel extraction and combustion. The necessity for academics to be mobile is entrenched through disciplinary norms and social values, as well as academic structures characterized by precarious work contracts and policies of internationalization, and is often reliant on highly polluting air transport. In the absence of climate-compatible techno-solutions enabling business-as-usual aeromobilities, we – the aeromobile publics – need to rethink our practices. These practices, and their unjust impacts, are incongruent with critical geographical scholarship. In this paper I begin to theorize just geographies of academic mobilities in the climate crisis. I do so by engaging with feminist climate justice, just mobilities and radical mobilities to consider the inequities within and beyond academic mobilities. I signal the ways that academic mobilities relate to broader patterns of education, labor market practices, and economic models, and how these together reinforce the discursive and lived power of the mobile academic work/life. I suggest that a starting point for just geographies of academic mobilities should be redressing asymmetries in geographies of knowledge production and signal 7 initial actions with the potential to initiate more just forms of climate changed academic mobilities.